Sankofa Urbanism: retrieval, resilience, and cultural heritage in cities through time - Campbell, Jacob; Bouman, Mark; Crawford, Arlene; Derby Lewis, Abigail (Frontiers in Ecology and Evolution, 2023)
One frequently cited principle that underlies the current move toward sustainability in urban planning and policy is, "long-term vision, incorporating awareness of the past and looking way into the future." We name this "Sankofa Urbanism," from the Ghanaian symbol and proverb that suggests, "it is not wrong to reach back for that which you have forgotten." Planners and policy-makers have sought to build in cultural heritage as an important feature of "nature-based solutions" for cities. We argue that retrievals from the past in multiple forms can strengthen the integration of biodiversity preservation, community place-making and urban sustainability initiatives. We present a case for broader examination of how the past, along with diverse forms of ancestral environmental knowledge, are deployed to design and realize sustainability plans. We also call for deeper consideration of how urban planning leverages the evidence of archeology and history. The paper features a case study from our work in the Chicago region where heritage-based activities have been developed as solutions to contemporary urban environmental problems.